Cycle engine modelling of spark ignition engine processes during wide-open throttle (WOT) engine operation running by gasoline fuel - Mohd Fadzil, Abdul Rahim; M. M., Rahman; R. A., Bakar (IOP Publishing, 2012)
One-dimensional engine model is developed to simulate spark ignition engine processes in a 4-stroke, 4 cylinders gasoline engine. Physically, the baseline engine is inline cylinder engine with 3-valves per cylinder. Currently, the engine's mixture is formed by external mixture formation using piston-type carburettor. The model of the engine is based on one-dimensional equation of the gas exchange process, isentropic compression and expansion, progressive engine combustion process, and accounting for the heat transfer and frictional losses as well as the effect of valves overlapping. The model is tested for 2000, 3000 and 4000 rpm of engine speed and validated using experimental engine data. Results showed that the engine is able to simulate engine's combustion process and produce reasonable prediction. However, by comparing with experimental data, major discrepancy is noticeable especially on the 2000 and 4000 rpm prediction. At low and high engine speed, simulated cylinder pressures tend to under predict the measured data. Whereas the cylinder temperatures always tend to over predict the measured data at all engine speed. The most accurate prediction is obtained at medium engine speed of 3000 rpm. Appropriate wall heat transfer setup is vital for more precise calculation of cylinder pressure and temperature. More heat loss to the wall can lower cylinder temperature. On the hand, more heat converted to the useful work mean an increase in cylinder pressure. Thus, instead of wall heat transfer setup, the Wiebe combustion parameters are needed to be carefully evaluated for better results.